Reconstructing Ecotheological Restorative Justice in Environmental Crime Prevention - Taufik Hidayat Simanjuntak; D K Dewi; Mospa Darma; Faisal Saddat Soadoun (International Journal For Advanced Research, 2026)
Environmental crime has become one of the most significant challenges to environmental protection because it has caused extensive ecological degradation, biodiversity loss, and long-term threats to sustainable development. The existing environmental criminal justice system has predominantly relied on punitive sanctions, which have not adequately restored damaged ecosystems or strengthened long-term environmental responsibility. This study aimed to reconstruct a comprehensive normative framework for environmental crime prevention by integrating restorative justice with ecotheological principles. The study employed a normative legal research approach using statutory, conceptual, comparative, and philosophical analyses. Data were collected through library research from legislation, judicial decisions, international legal instruments, and scholarly publications concerning environmental criminal law, restorative justice, environmental ethics, and sustainability. The collected legal materials were analyzed qualitatively using prescriptive legal reasoning to identify conceptual limitations and formulate a reconstructed legal framework. The results showed that the prevailing retributive justice model remained insufficient to address the multidimensional impacts of environmental crime because it primarily emphasized punishment rather than ecological restoration and community recovery. The reconstructed framework integrated ecological restoration, moral responsibility, community participation, intergenerational justice, and sustainable environmental governance into a unified legal approach. The study concluded that integrating restorative justice with ecotheological principles provided a more comprehensive normative framework for environmental crime prevention by promoting ecological recovery, ethical accountability, and sustainable environmental governance.